Dos autos de defloramento às postagens virtuais: a construção discursiva da mulher em crimes sexuais – permanências e rupturas - Azevedo, Illa Pires de (2023)
This work is inserted within the scope of discursive studies and has as main goal to investigate how, by discourse, the image of women in legal actions. Thus, it starts from the principle that the relationship of the subject with their body – or with the bodies – is not clear to them, and focuses on the analysis of deflowering records dated from the early twentieth century (Queiroz, 2018) and materialities of 21st century (Bahia Forensic Electronic Magazine 2019, 2020). Seeking to meet the proposed goals, we move here the sense of hymen, as a biological mark of female virginity, to insert it within a historical functioning, which IS, in turn, regulated by a discursive memory, which still regulates female sexuality. Thus, anchored in the theoretical-methodological contribution of the French line discourse analysis, philosopher Michel Pêcheux (1990, 2009, 2010) and other scholars of the same theoretical aspect as the author: Eni Orlandi (2007, 2011, 2012), Freda Indursky (2009, 2011, 2013), Suzi Lagazy (1988), among others, will be analyzed the discursive formations and ideological about the woman conveyed in these documents, as well as the functioning of discursive memory, observing how these subjects are discursively characterized in these processes. To this end, the social elements, ideologies, history, the conditions of production of discourse were considered, based on the idea that discourses are not fixed, but change and follow the social human transformations, therefore being constituted in history and for history. It was also considered the fact that the language is opaque and not transparent, and that there is no direct relationship between the sign and the referent. Thus, the reading gestures made here allowed us to observe that body and subject are imbricated in the discursive process, so that the body means, materializes and circulates in different ways from different significant, being interpreted by distinct subjects and occupying different places in the speech. Given the documents analyzed, it can be said that women victims of sexual crimes mean as being tarnished and the legal institutional space in which they are heard presupposes a public exposure of their bodies. In addition to flesh, there are history, ideology and subjectivity working and circulating meaning effects and enabling the words. Speeches about the virginity and subjectivation of women recovered in the analyzes corpora reaffirm certain constructions on sexuality and female body. Biologically, there is an equal body for all women; Ideologically, there is not. The dominant discourse of male virility and the emerging sexual desires of man, just as the blame of women have been recovered and attests different subjectivations for men and women and their respective bodies. Other positions about women have also been silenced, so that the silence imposed on victims resonate positions that support distinct discursive formations, as it works for the meaning contradiction game. On the one hand, the Speech of Law; On the other, the victim and the accused. In the middle, silence policies giving them meaning.